45. PREGNANCY OUTCOMES IN PATIENTS WITH FROZEN BLASTOCYST TRANSFER USE OF TIME-LAPSE INCUBATOR WITH AND WITHOUT PGT-A AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate pregnancy outcomes in patients with frozen blastocyst embryo transfer cultured using the Timelapse system with and without preimplantation genetic testing for aneuploidy (PGT-A) at Hanoi Obstetrics and Gynecology Hospital.Materials and methods: This cross-sectional descriptive study was conducted on 221 patients who underwent single day-5 frozen embryo transfer using the Timelapse system at Hanoi Obstetrics and Gynecology Hospital, from June 2023 to May 2024.Results: The rate of bHCG (+), clinical pregnancy rate, and progressive pregnancy in the non-PGT group and the group with normal PGT results were significantly higher than in the group with abnormal PGT results (p< 0.05).. The difference between the 3 groups was not statistically significant (p>0.05). The pregnancy rate in ICM type A (70%; 53.9%; 71.4%) was higher than that in type B (30%; 46.1%; 28.6%) and C (0%; 0%; 0%) in all 3 groups: no PGT, normal PGT and abnormal PGT. The pregnancy rate in TE type A (61.4%) was higher than that in type B (38.6%) and C (0%) in the group that did not do PGT. The pregnancy rate in TE type B (55.3%; 71.4%) was higher than that in type A (36.8%; 28.6%) and C (7.9%; 0%) in both groups that did PGT with normal results and abnormal PGT.Conclusion: Pregnancy outcomes in patients undergoing day-5 frozen embryo transfer cultured using the Timelapse system without PGT-A or with normal PGT-A results are superior to those with abnormal PGT-A results (p > 0.05).
Keywords: Frozen; blastocyst embryoư; time-lapse incubatorư; PGT-A